Sedimentary processes in the bottom boundary layer of a contourite drift in the northern South China Sea - Wu, Longwei; Zhao, Yulong; Liu, Zhifei; Ma, Pengfei; Zhang, Yanwei (Frontiers in Marine Science, 2023)
Ocean dynamic processes in the bottom boundary layer (BBL) are crucial for sedimentation, such as deposition and resuspension of marine sediments. In this study, we conducted in-situ tripod observations of the sediment ridge of a contourite drift in the northern South China Sea to understand the main dynamic processes affecting sedimentation on the contourite drifts. It was found that the diurnal tidal current was the strongest current at the study site, thus acting as the main dynamic affecting sedimentation processes. Periodic events of elevated suspended sediment concentration (SSC) were observed, some of which occurred only within 15 m above the seafloor and were termed near-bottom high SSC events, while others covered the entire range of the observed water column and were termed full-depth high SSC events. In-situ sediment resuspension at the sediment ridge is not an important factor affecting the formation of high SSC events. Rather, these high SSC events were mainly caused by lateral transport of sediments from the main body of the contourite drift by the northwestward diurnal tidal currents. The seafloor sediments at the main drift body are resuspened owing to the near-critical reflection of diurnal tidal currents on the slope topography of the drift. During periods when diurnal tidal currents were weak, locally generated internal waves could also induce burst-like full-depth high SSC events. This study highlights the diurnal tidal current as the main dynamic regulating the sedimentary processes of the contourite drifts in regions where the near-critical reflection prone to occur, implying the complexity of sediment dynamics of contourite drifts.